A comprehensive review on unitized regenerative fuel cells: Crucial challenges and developments. (16th February 2017) - Sadhasivam, T.; Dhanabalan, K.; Roh, Sung-Hee; Kim, Tae-Ho; Park, Kyung-Won; Jung, Seunghun; Kurkuri, Mahaveer D.; Jung, Ho-Young
Abstract: From extensive reported analyses, we reviewed the limitations, challenges, and advanced developments of the materials and components mainly used in the unitized regenerative fuel cell (URFC) system. URFC is a viable energy storage system owing to its high specific packaged and theoretical energy densities of 400–1000 Wh/kg and 3660 Wh/kg, respectively. Nevertheless, during the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), the stability and durability of the URFC unit cell was severely affected by various degradation factors in the stacked cell. The certain issues are related to the (i) electrocatalysts (high cost, aggregation, migration, and supportive material corrosion), (ii) dissolution and cracks in the Nafion binder, (iii) physical degradation and higher cost of polymer membrane, and severe carbon corrosion in (iv) gas diffusion packing and (v) bipolar plates. Among these factors, the critical challenges are the severe carbon corrosion and durability of the membrane in the unit cell regions. The degradation occurs in the supporting material of the electrocatalyst, gas diffusion packing, and bipolar plate owing to carbon corrosion because of the high applied potential in the water electrolyzer mode. Recent developments are significantly enhancing the durability and overcoming the limitations in the URFC system. In this comprehensive review, we have pointed out the limitations, challenges, and critical developments in URFC systems. Furthermore, built on our experimental and intellectual awareness in the context of URFC system developments, new strategies have been suggested to prepare novel structured materials and composites for advanced URFC applications. Highlights: URFC is an optimum fuel cell system owing to its specific high energy density. Critical problem is severe carbon corrosion in electrocatalyst support and GDB, BP. Major challenges are cost and durability of the membrane and electrode assembly. Highly crystalline of Gr-carbon can be considered as a corrosion-resistant material. Novel structured and low cost materials are most promising to advanced URFC system.